Raised incidence of autoimmune thyroiditis among females in 2nd, 3rd and 4th decades: a randomized study - V. K., Rajan (International Surgery Journal, 2019)
Background: Autoimmune thyroid disease (AITD), a mutual organ specific autoimmune disorder is seen mostly in women between 30-50 years of age. The rationale behind the study is to determine increased incidences of auto immune thyroiditis. The objective of the present study was to evaluate the incidence of autoimmune thyroiditis and thyroid dysfunction in healthy females with no previously known thyroid disease, in an urban area. Methods: The study was conducted on female volunteers with no known thyroid disease. 370 subjects among the hospital’s medical and administration personnel were recruited. All underwent thyroid ultrasound (US) and thyroid anti-peroxidase (TPOAb) and anti-thyroglobulin (TgAb) antibodies were measured. Hypoechogenicity and thyroid volume were determined by sonography. Results: the incidence of autoimmune thyroiditis was 23.2% and 20-30 years were most commonly affected (P = 0.008); when including cases of atrophic thyroid, the frequency decreased to 14.7%. Conclusions: The frequency of autoimmune thyroiditis is clearly elevated in the studied population. Further studies are necessary in order to define the increased incidence of autoimmune thyroid disease.